Development of 14C Dating of Mortars at ETH Zurich. Issue 3 (2nd June 2020) - Hajdas, Irka; Maurer, Mantana; Röttig, Maria Belen
ABSTRACT: The ages of mortars and plaster can help reveal the history of monuments, their construction, or restoration times. However, these anthropogenic carbonates pose a challenge when it comes to separation of the atmospheric radiocarbon ( 14 C) signal of the CO2 fixed in the mortar at the time of consolidation, i.e., the time of binder formation. The variety and heterogeneity of mortars require individual assessments of each sample and 14 C results. Here we present our current preparation method and summarize experience based on results collected during the last 20 years of mortar dating at the ETH laboratory.